An embedded system for evoked biopotential acquisition and processing - Garcia, Pablo Andres (2014)
This work presents an autonomous embedded system for evoked biopotential acquisition and processing. The system is versatile and can be used on different evoked potential scenarios like medical equipments or brain computer interfaces, fulfilling the strict real-time constraints that they impose. The embedded system is based on an ARM9 processor with capabilities to port a real-time operating system. Initially, a benchmark of the Windows CE operative system running on the embedded system is presented in order to find out its real-time capability as a set. Finally, a brain computer interface based on visual evoked potentials is implemented. Results of this application recovering visual evoked potential using two techniques: the fast Fourier transform and stimulus locked inter trace correlation, are also presented.